1983
DOI: 10.3109/03005368309107879
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Development and Maturation of the Hearing System; A Critical Review Article

Abstract: The understanding of development and maturation of the auditory system is essential for many reasons, including the practical aspects of auditory behaviour, testing, and teaching a hearing-impaired child to communicate effectively. The study of maturation of the auditory system is gaining increasing importance also because it should help us to interpret correctly certain aspects of auditory behaviour in infants. When studying the auditory system we should not be concerned solely with development of function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Adequate auditory stimulation, in early childhood in particular, is the foundation for optimal speech and language development as well as the acquisition of literacy skills [1,2]. Failure to detect early and effectively manage within the first year of life a permanent hearing impairment that is congenital or that originates in the neonatal period has been associated with significant and irreversible deficits in speech and in linguistic, cognitive, and educational development [3,4].…”
mentioning
confidence: 99%
“…Adequate auditory stimulation, in early childhood in particular, is the foundation for optimal speech and language development as well as the acquisition of literacy skills [1,2]. Failure to detect early and effectively manage within the first year of life a permanent hearing impairment that is congenital or that originates in the neonatal period has been associated with significant and irreversible deficits in speech and in linguistic, cognitive, and educational development [3,4].…”
mentioning
confidence: 99%
“…The median PTT of 50 dB HL at 2000–4000 Hz (as recorded at ≈11 years of age) was similar to the median ABRthr at birth, i.e., 50 dB nHL. This similarity might reflect stable hearing thresholds—on a group level—if the neural maturation, which affects hearing sensitivity [ 13 , 14 ] in a frequency-dependent way at postsynaptic levels [ 73 ], outbalances the acoustical effect of the growth of the outer ear canal [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were 9–13 years old at the time of inclusion. The reason for choosing this study group, recruited from [ 11 ], was the well-defined material of consecutively identified SNHLs at birth, no problem with acoustical effects due to growth of the outer ear canal [ 12 ] or neural maturation in a frequency-dependent way [ 13 , 14 ] as in young children, and the opportunity to use advanced psychoacoustical tests and questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…The vestibular structures are well developed at birth, however they do continue to mature postnatally (Fisch, ). The number of hair cells in all five structures increases from PND0 to PND3 then decreases again from PND3 to PND7, which coincides with ongoing hair cell apoptosis that starts at E19, reaches a peak at PND3 to decrease again around PND7 (Zheng & Gao, 1997).…”
Section: Development and Innervation Of The Inner Earmentioning
confidence: 99%